STUDIES ON THE ANTIGENIC PROPERTIES OF COMPLEMENT : I. DEMONSTRATION OF AGGLUTINATING ANTIBODIES AGAINST GUINEA PIG COMPLEMENT FIXED ON SENSITIZED SHEEP ERYTHROCYTES - Klein, Paul G. (The Rockefeller University Press, 1960)
Evidence is presented to show that guinea pig complement fixed on sensitized sheep red cells acts as a specific agglutinogen. Agglutinating antibodies that react with cell-fixed complement can be produced by immunizing rabbits with a complex of stromata-amboceptor-complement or with guinea pig serum globulin. These agglutinins can be removed by precipitation with guinea pig serum. They are, therefore, distinct from immunoconglutinins.